(3GdfLOjGJs - (3GdCHjhQOj , eMeO Hf CMeO Hf eMeO GdbQTj, CHh GdeXaQ,J (B507 (3g` s ((3Uai Hf Ydi Hf CMeO Hf MeRI Hf CMeO Hf ehSi Gdgei s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Ef CMb eG JUQa Edjg Gdgee hJfJgR aQU GdGecGf ajg hJZJfe MeO Gddg WabJ GfXe GdTYQ ajeG GTchG Hg fHhI GdReGf s
(3BNQgG (B:s
(3ef UaG dCNjg WhjI hde jcf GdZOQ ajg SLjI hbO LHd Ydi gPg GdTjeI hgh ai GdeTjeI s
(3GdfSNI HgG MhGTs
(3HChdg bQGAGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B314s
Keywords: (3GdCOHs